Optimization of food waste utilization in the RDF recovery energy facility - Abdul Rashid, Zulkifli; Alias, Azil Bahari; Ku Hamid, Ku Halim; Wan Omar, W. A.; Wan Abdul, K. G. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
It is well known that there is a significant increased in the quantity of Municipal Solid Waste (MSW) generated every year. Therefore, the management of MSW must be handled carefully by experts. Malaysia as one of the developing country with population nearly 30 millions also facing problems related to MSW management and this issue is quite critical. Even though various programmes were established and few model technologies were introduced by the government to manage MSW effectively, but the impact remain unsatisfaction. For example, the energy facility recovery project which use MSW gathered around Kajang as an alternative fuel still not successful to provide energy according to the design capacity of that particular facility. This failure was observed due to the impact composition of MSW collected which consists huge amount of food waste (57%), 16% plastic, 15% diaper, 9% mixed papers and the remaining 3% textile. The existing process technology at Refused Derived Fuel (RDF) facility is no designed to create a new economic benefit from abundant incoming food waste to the facility. Therefore in this paper, the analysis and suggestion of technology on existing RDF recovery energy facility will be discussed especially on how to overcome the abundant composition of food waste.